Numerical study of long wave runup on a conical island - Phung, Dang Hieu (Đại học Quốc gia Hà Nội, 2014)
A numerical model based on the 2D shallow water equations was developed using the Finite Volume Method. The model was applied to the study of long wave propagation and runup on a conical island. The simulated results by the model were compared with published experimental data and analyzed to understand more about the interaction processes between the long waves and conical island in terms of water profile and wave runup height. The results of the study confirmed the effects of edge waves on the runup height at the lee side of the island.